Auditoría de gestión al Gobierno Provincial De Zamora Chinchipe periodo 2012 - Heras León, Fernanda Graciela (2016)
This thesis entitled " Performance Audit GOVERNMENT PROVINCIAL DE ZAMORA CHINCHIPE PERIOD 2012" , whose objectives were aimed at : assessing the internal control system and the degree of compliance with the institutional mission and vision , apply performance indicators to measure the standards of efficiency, effectiveness and economy of the company and finally structure the Final audit Report to be presented to the Lord Prefect Sclgo . Quishpe Salvador Lozano , containing the same opinions , conclusions and recommendations as a basis for successful decision making. To fulfill these objectives the audit process issued by the Comptroller General of the State through its manual Auditing applicable to public institutions was conducted , begins with the Preliminary Knowledge where we make the observation to the entity and interviews allowing top officials about the activities taking place and the difficulties being experienced , as well as meet the institutional mission and vision ; in Planning is reviewed and analyzed the documentation provided by the entity that allows us to perform the evaluation of internal control component and determine the qualification of audit risk factors , then the execution in which audit programs developed to apply each component all this information collection management possible to measure in terms of efficiency , effectiveness and economy in the institution. To end the Final Result Communication Audit Report containing the same opinions , conclusions and recommendations to improve corporate governance based on the findings identified in the previous phase is drawn ; we can conclude that as a result of the audit to the Provincial Government of Zamora Chinchipe include in the Talent there is no institutional code of ethics, there is no manual functions , not constants to facility staff training is provided , records of officials of the institution is not updated , the staff know the institutional mission and vision ; Financial Appeal in self-management activities are limited , the budget is allocated by the government does not fully cover the proposed activities , the staff of the institution is not caucionado ; in Resource Material not have a systematic record of the property , the physical space for the receipt thereof is reduced and finally not take control of the distribution of materials. Finally the goals outlined in this thesis were met , as their results contribute to the improvement and development of the institution.